2017
DOI: 10.1134/s0021364017100095
|View full text |Cite
|
Sign up to set email alerts
|

High rotatable magnetic anisotropy in MnBi thin films

Abstract: 1 Институт физики им. Л.В. Киренского, ФИЦ КНЦ СО РАН, Красноярск, Россия 2 Сибирский федеральный университет, Красноярск, Россия 3 Институт химии и химической технологии, ФИЦ КНЦ СО РАН, Красноярск, Россия a) miagkov@iph.krasn.ru АбстрактРассмотрены изменения структурных и магнитных свойств трехслойных пленочных систем Bi/Mn/Bi и Mn/Bi/Mn эквиатомного состава в процессе вакуумного отжига. Отжиг пленок Bi/Mn/Bi при температуре 270С в течение часа приводит к синтезу хорошо исследованной высоко ориентированной … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Although highly oriented or epitaxial thin films have been mainly studied for the magnetic anisotropy, recent developments have revealed that “randomly‐oriented polycrystalline” films made of the large κ system (due to the strong magneto‐crystalline anisotropy of K > 10 5 –10 6 J m −3 ) show the omni‐directional domain arrangement in any spatial direction (Figure 1c). [ 6–8 ] The electrical responses such as anomalous Hall and Nernst effects are empirically known to be proportional to the magnetization in conventional FMs. [ 9 ] Therefore, the larger the magnetization is, the larger the response becomes.…”
Section: Introductionmentioning
confidence: 99%
“…Although highly oriented or epitaxial thin films have been mainly studied for the magnetic anisotropy, recent developments have revealed that “randomly‐oriented polycrystalline” films made of the large κ system (due to the strong magneto‐crystalline anisotropy of K > 10 5 –10 6 J m −3 ) show the omni‐directional domain arrangement in any spatial direction (Figure 1c). [ 6–8 ] The electrical responses such as anomalous Hall and Nernst effects are empirically known to be proportional to the magnetization in conventional FMs. [ 9 ] Therefore, the larger the magnetization is, the larger the response becomes.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic easy axis of MnBi alloy with Pd 1/2 and Rh remains the same as bulk MnBi and lies out-of-plane direction, while the magnetic-easy-axis of MnBi alloy with Li, O, Pd and Pt lie in-plane. Pd can rotate the magnetic-easy-axis 40 from in-plane to out-of-plane depending upon the percentage of Pd that would be incorporated in MnBi. We anticipate this comprehensive study of MnBi alloy spurs more theoretical and experimental study.…”
mentioning
confidence: 99%